Suppose $E,F$ are real Banach spaces, $U \subset E$ is open and $f: U \to F$ is a differentiable. Further suppose that two points $x,y \in U$ are such that the line segment between them is contained in $U$, so that if $h$ denotes the map $\mathbb{R} \to E \, ; \, t \mapsto (1-t)x + ty$ then $h([0,1]) \subset U$.

I'm reading a proof that claims, under the hypotheses written above, there exists some $t_0 \in (0,1)$ for which the point $x_0 = h(t_0)$ satisfies

$ \| f(y) - f(x) \| \leqslant \| Df(x_0)(y - x) \| \leqslant \| Df(x_0) \| \| y - x \|$.

The proof starts off as follows: "Using the Hahn-Banach Theorem, choose $\phi$ in the conjugate space $F^*$ of $F$ so that $\| \phi \| = 1$ and $\|f(y) - f(x) \| = \phi( f(y) - f(x) )$."

From there the proof simply applies the mean value theorem to $\phi \circ f \circ h : [0,1] \to \mathbb{R}$, using the chain rule along the way.

I'm assuming by "conjugate space" he means the space $F^* = L(F,\mathbb{R})$ of continuous linear functionals $F \to \mathbb{R}$.

How does the Hahn-Banach Theorem allow the author to choose $\phi$ as they did? It might be a stupid question, but I've never used the Hahn-Banach Theorem, and frankly only heard of it a week or so ago. I've seen a proof of a formulation, which I can follow, but from what I hear there are different formulations of the theorem.


I assume $f(y)\neq f(x)$. If $f(y)=f(x)$ the inequality is trivially true. Consider the linear function $h$ define on the line $L=Vect(f(y)-f(x))$, such that $h(f(y)-f(x))=\|f(y)-f(x)\|$, it is bounded and its norm is $1$ since $h({{f(y)-f(x)}\over{\|f(y)-f(x)\|}})=1$. Hahn Banach implies you can extend $h$ to $\phi:F\rightarrow R$ such that $\phi(f(y)-f(x))=\|f(y)-f(x)\|$ and $\|\phi\|=1$.

  • $\begingroup$ So $L$ is the span in $F$ of the fixed vector $z = f(y) - f(x)$, but how is $h$ defined? Are you using the fact that $L$ has a basis consisting of a single element $z$, assigning $h:z \mapsto \| f(y) - f(x) \| \in \mathbb{R}$ and then extending $h$ to a map $L \to \mathbb{R}$ linearly? $\endgroup$ – joeb Feb 1 '17 at 2:38
  • $\begingroup$ exactly, I am using this fact. $\endgroup$ – Tsemo Aristide Feb 1 '17 at 2:39
  • $\begingroup$ I think I get it now. If $\tilde{z} = tz \in L$ is such that $1 =\| \tilde{z} \| = |t| \| z \|$ then $| h(\tilde{z}) | = |th(z)| = |t||z| = 1$ so that $\| h \| = \sup \{|h(\tilde{z})| : \| \tilde{z} \| = 1 \} = \sup\{1\} = 1$. Then apply the Hahn-Banach Theorem as you said. Thanks so much $\endgroup$ – joeb Feb 1 '17 at 2:48

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.